Creating a Canopy of Civic Security for Women in Cities (District 12 of Tehran) - Kanaani, Choman (Digital Transformation and Administration Innovation, 2025)
The purpose of this study is to examine the status of District 12 of Tehran in terms of women’s security indicators and to identify the most important factors reducing women’s security in this district. This research is descriptive–analytical in method and applied in purpose. Data were obtained through the distribution of questionnaires among 38 women residing in District 12 of Tehran. The results were analyzed using Spearman’s correlation coefficient, exploratory factor analysis, and Friedman’s test in the SPSS environment. Field survey results indicate that, based on the average of 10 research indicators, women’s security in 7 dimensions—including physical, structural, functional, urban management, urban furniture, urban transportation, and cultural–social dimensions—is below 3. This indicates that the status of various indicators related to women’s security in District 12 of Tehran is unfavorable. Moreover, the status of three dimensions—urban quality of life, accessibility, and behavioral—is at a relatively moderate level. The correlation coefficient between dimensions also shows that accessibility and quality of life are correlated with the behavioral dimension; the cultural–social dimension is correlated with urban management and urban furniture; and the physical dimension is correlated with the structural dimension. These correlations are at a moderate and positive level. Therefore, any weakness in one dimension can negatively affect its corresponding dimension, thereby reducing overall women’s security in District 12 of Tehran. As a result of exploratory factor analysis, latent factors or constructs within the 10 dimensions of women’s security were extracted, and 15 factors underlying the 59 research variables were identified. The final 15 extracted factors were able to explain 47.01% of the variance of all research variables. In each factor, among the 15 factors derived from factor analysis, most variables with higher factor loadings were related to physical, urban furniture, urban quality, and accessibility issues. A comparison of dimension averages using the one-sample t-test showed that the women’s security index, with a significance level of less than 0.05, is not in a better situation. Furthermore, the results of Friedman’s test showed that the structural and urban furniture dimensions ranked eighth and ninth in mean rank, respectively. Therefore, it can be said that these two dimensions play a major role in reducing women’s security compared to other dimensions. Overall, the status of women’s security indicators in District 12 of Tehran is unfavorable. Moreover, the structural and urban furniture factors are the most important contributors to the reduction of women’s security in urban spaces in District 12 of Tehran and should receive special attention from urban managers to improve women’s security in urban spaces. Among the indicators affecting women’s security in urban spaces, the structural and urban furniture dimensions play a significant role in enhancing both the subjective and objective aspects of women’s security. Organizing urban spaces in these dimensions can greatly contribute to increasing the sense of security among citizens, particularly women.